Efek Ekstrak Arbei (Rubus idaeus) terhadap Kadar Kolesterol Total Tikus Wistar Model Sindrom Metabolik - Danus Hemawan; Sarsono Sarsono (Syntax Corporation Indonesia, 2024)
Metabolic syndrome is characterized by low HDL levels, high triglycerides, hypertension, increased blood glucose, and obesity, often associated with obesity and type 2 diabetes. This study aimed to investigate the effect of Wild Red Raspberry (Rubus idaeus) on total cholesterol levels in Wistar rats (Rattus norvegicus) with a metabolic syndrome model. Method This research employed a quantitative experimental laboratory study with a pretest-posttest control group design. A total of 30 male Wistar rats were divided into five groups: K1 (negative control), K2 (positive control), and K3, K4, K5 (metabolic syndrome) treated with Rubus idaeus extract at doses of 30 mg/200gBW/day, 60 mg/200gBW/day, and 90 mg/200gBW/day. Total cholesterol levels were measured on days 8, 36, and 64. Data analysis was performed using Shapiro-Wilk normality test, and the results were not normal in distribution and hemogenity although after transformatted, so non-parametric tests Kruskal-Wallis, were used, followed by Mann-Whitney tests. Result ,the administration of Rubus idaeus extract resulted in the highest total cholesterol levels in group K3 and the lowest in group K5. Statistical analysis showed significant differences (p < 0.05) before and after treatment in each group, with Pearson correlation tests demonstrating a very strong relationship between the dosage of Rubus idaeus and total cholesterol levels. Conclusion, the administration of Rubus idaeus extract significantly reduces total cholesterol levels, with the dose of 90 mg/200gBW being the most effective in lowering total cholesterol levels.